PENGARUH MODEL SIKLUS BELAJAR 5E PADA PRAKTIKUM KOLOID TERHADAP HASIL BELAJAR SISWA KELAS XI MIA SMA NEGERI 2 PONTIANAK - Syafitri Mayang Sari; Rody Putra Sartika; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis research aimed to find out the difference between learning result of the students who were taught by learning cycle model 5 E and those who were taught by conventional learning model as well as to know the effect of learning cycle model 5 E towards learning result of the eleventh grade students in the Coloid experiment at SMA Negeri Pontianak. The sampling system was purposive sampling which XI MIA 3 was choosen as experimental class and XI MIA 2 was choosen as control class. The instruments used were the test of learning result and observation sheets to measure the learning result of the affective and students’ psychomotor. The result of this research showed that the students who were taught by learning cycle model 5 E had the mean score of cognitive, affective and psychomotor learning results were 86,84; 52,63 and 63,15 respectively. Meanwhile the students who were taught by conventional learning model had the mean score of cognitive, affective and psychomotor learning results were 78,94; 42,10 and 52,63 respectively. Hence, it could be concluded that learning cycle model 5E affected on the improvement of students’ learning result which was 28,52 %.Keywords : Learning result, Coloid experiment, learning cycle model 5 E